The Effect of Rebranding Strategy on Corporate Image: A Case Study of PT. Goto Gojek Tokopedia Tbk - Melda Dea Safitri; Nurul Aini; Agung Augustrianto; Nasihatun Falah; Tari Fitrianti; Siti Indriani (Dinasti International Journal of Management Science, 2026)
This study is motivated by the rapid development of the digital industry which requires companies to adapt through rebranding strategies to maintain competitiveness and improve corporate image. The objective of this research is to analyze the effect of rebranding strategy on corporate image at PT GoTo Gojek Tokopedia Tbk. The research method uses a quantitative approach with an associative research type. Data were collected through questionnaires using a Likert scale from 30 respondents selected through purposive sampling technique. Data analysis techniques include validity test, reliability test, classical assumption test, and simple linear regression analysis. The results show that the rebranding strategy has a positive and significant effect on corporate image, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.626. In addition, the coefficient of determination value of 0.407 indicates that the rebranding strategy explains 40.7% of the variation in corporate image. Therefore, it can be concluded that an effective rebranding strategy significantly improves corporate imagen.